1998
DOI: 10.1007/s000110050310
|View full text |Cite
|
Sign up to set email alerts
|

Novel pathways for glucocorticoid effects on neutrophils in chronic inflammation

Abstract: Neutrophils have been implicated in mediating much of the tissue damage associated with chronic inflammatory diseases such as rheumatoid arthritis, where they are involved in destruction of both cartilage and bone. Glucocorticoids are powerful anti-inflammatory agents, often used in the treatment of this autoimmune disease. They exert significant inhibitory effects on neutrophil activation and functions, such as chemotaxis, adhesion, transmigration, apoptosis, oxidative burst, and phagocytosis. The mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 56 publications
1
60
1
3
Order By: Relevance
“…On the other hand, glucocorticoid (corticosterone) is known to induce the mobilization of neutrophils from the bone marrow into the circulating blood ( 24 ), inhibit apoptosis of circulating neutrophils ( 25 ) and suppress the inflammatory consequences of neutrophil migration and activation ( 26 ). In the present study, however, serum corticosterone concentrations in the DHC and CAP groups at 3 h did not change significantly as compared with the CON group.…”
Section: Acute Effects Of Cap and Dhc On The Number Of Neutorophils Acontrasting
confidence: 68%
“…On the other hand, glucocorticoid (corticosterone) is known to induce the mobilization of neutrophils from the bone marrow into the circulating blood ( 24 ), inhibit apoptosis of circulating neutrophils ( 25 ) and suppress the inflammatory consequences of neutrophil migration and activation ( 26 ). In the present study, however, serum corticosterone concentrations in the DHC and CAP groups at 3 h did not change significantly as compared with the CON group.…”
Section: Acute Effects Of Cap and Dhc On The Number Of Neutorophils Acontrasting
confidence: 68%
“…Using this methodology, we found that mature marrow granulocytes (band cells, segmented cells) were able to adequately carry out phagocytosis, produce superoxide, and respond to chemotactic factors subsequent to the Gc exposure. This is in marked contrast to many previous studies where exposure of peripheral neutrophils to pharmacological steroids was shown to alter their function (17). To carry out these studies, CS was delivered to mice continuously via tablet implant to mimic chronic stress events.…”
Section: Discussionmentioning
confidence: 96%
“…Use of more stable, short N-terminal derived peptides has helped overcome this problem. Indeed, peptide Ac2-26 inhibited phagocytosis of immune complexes (Goulding et al 1998) as well as superoxide generation (Euzger et al 1999) by human monocytes.…”
Section: Anxa1 Actions On Monocytes and Macrophagesmentioning
confidence: 98%